Excess Risk of Lung Cancer Among Agriculture and Construction Workers in Indonesia - Anna Suraya; Dennis Nowak; Astrid Widajati Sulistomo; Aziza Ghanie Icksan; Ursula Berger; Elisna Syahruddin; Stephan Bose-O'Reilly (Ubiquity Press, 2021)
Background:In Indonesia, many occupations and industries involve a variety of hazardous and toxic materials. The ILO estimates that about 21.1% of the tracheal, bronchial, and lung cancer deaths among men were attributable to workplace hazardous substances. This study investigated the relationship between occupations or workplace exposure and the risk of lung cancer in the country. The results will help determine how Indonesia can best mitigate the risk for its workers. Objectives:This case-control study utilizes the Indonesian Standard of Industrial Classification (IndSIC) 2015 with the aim of exploring the risk of lung cancer among Indonesian workers. Methods:The study included patients aged 35 years old or older receiving thoracic CT at the radiology department of Persahabatan Hospital. The cases were histological confirmed primary lung cancers, while the controls were negative thoracic CT scan for lung cancer. The subjects' job titles and industries were classified according to IndSIC 2015 and blind to the patient's grouping as a case or control. Logistic regression was used to determine the odds ratios for lung cancer among all sections and some divisions or groups of IndSIC 2015. Findings: The mean age was 58.1 (±10.23) years for lung cancer patients and 54.5 (±10.23) years for controls. The majority of subjects (19.6%) worked in Section G (Wholesale and retail trade; repair of motor vehicles and motorcycle). After adjusting for age, gender, level of education, and smoking habit, the risk of lung cancer was nearly three-times higher (OR = 2.8, 95% CI = 1.11-7.02) in workers of Division A01 (crop, animal production, and hunting) and two-times higher (OR = 1.9, 95% CI = 1.05-3.46) in workers of Section F (construction) compared to the workers in other sections or divisions. Conclusions:The excess risk of lung cancer among certain categories of workers confirms the need for improved policy, monitoring, and control of occupational exposure for primary cancer prevention and workers' compensation purposes.